Sorogan Pendampingan Baca Al Qur’an Sorogan Dalam Meningkatkan Bacaan Tartil Bagi Anak-Anak Desa Pakis Kecamatan Kunjang - Komaru Zaman; Achmad Riduwan; Ahmad Zaenulloh; Moh. Agus Aris Maulansyah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The ability to read the Qur'an with tartil (proper recitation) is an obligation for every Muslim. However, reality shows that many Muslim children, especially in rural areas, are still unable to read the Qur'an correctly. Pakis Hamlet in Pakis Village, Kunjang District, faces similar issues, with factors such as a lack of competent teachers, limited learning facilities, and low motivation among children to learn the Qur'an. To address these problems, a Qur'an reading assistance program was implemented using the sorogan method integrated with modern learning approaches. This study aims to implement and evaluate the effectiveness of the program in improving the ability to read the Qur'an with tartil among children in Pakis Hamlet. Using the Participatory Action Research (PAR) method, this study actively involved the community in every stage, from initial mapping to program evaluation. Data was collected through participatory observation, in-depth interviews, focus group discussions (FGDs), and documentation. The results show significant improvements in children's Qur'an reading abilities, including reading fluency, tajwid accuracy, and understanding of verse meanings. The program also positively impacted children's psychological and social aspects, as well as increased awareness and participation of parents and the community in Qur'anic education. The sorogan method integrated with modern learning approaches proved effective in overcoming existing obstacles. Collaboration between the research team, community leaders, and various stakeholders was key to the program's success. This research provides theoretical and practical contributions to the development of Qur'anic learning in rural areas and offers a community service model that can be replicated in other areas with similar characteristics